Standardisation of pathogenicity classification for somatic alterations in solid tumours and haematologic malignancies. (December 2021) - Koeppel, Florence; Muller, Etienne; Harlé, Alexandre; Guien, Céline; Sujobert, Pierre; Trabelsi Grati, Olfa; Kosmider, Olivier; Miguet, Laurent; Mauvieux, Laurent; Cayre, Anne; Salgado, David; Preudhomme, Claude; et al.
Abstract: Background: The difficulty in interpreting somatic alterations is correlated with the increase in sequencing panel size. To correctly guide the clinical management of patients with cancer, there needs to be accurate classification of pathogenicity followed by actionability assessment. Here, we describe a specific detailed workflow for the classification of the pathogenicity of somatic variants in cancer into five categories: benign, likely benign, unknown significance, likely pathogenic and pathogenic. Methods: Classification is obtained by combining a set of eight relevant criteria in favour of either a pathogenic or a benign effect (pathogenic stand-alone, pathogenic very strong, pathogenic strong, pathogenic moderate, pathogenic supporting, benign supporting, benign strong and benign stand-alone). Results: Our guide is concordant with the ACMG/AMP 2015 guidelines for germline variants. Interpretation of somatic variants requires considering specific criteria, such as the disease and therapeutic context, co-occurring genomic events in the tumour when available and the use of cancer-specific variant databases. In addition, the gene role in tumorigenesis (oncogene or tumour suppressor gene) also needs to be taken into consideration. Conclusion: Our classification could contribute to homogenize best practices on somatic variant pathogenicity interpretation and improve interpretation consistency both within and between laboratories. Highlights: Assessing pathogenicity of tumour variants with a systematic approach. Connecting with the ACMG/AMP guidelines for germline variants. Encompassing somatic specific criteria.